Comparison of fludarabine/melphalan (FM140) with fludarabine/melphalan/BCNU (FBM110) in patients with relapsed/refractory AML undergoing allogeneic hematopoietic cell transplantation - a registry study on behalf of the EBMT Acute Leukemia Working Party - Duque-Afonso, Jesús; Finke, Jürgen; Ngoya, Maud; Galimard, Jacques-Emmanuel; Schetelig, Johannes; Eder, Matthias; Rösler, Wolf; Bug, Gesine; Neubauer, Andreas; Edinger, Matthias; Wulf, Gerald G; Jindra, Pavel; et al. (Bone marrow transplantation, 2025)
The treatment of relapsed/refractory acute myeloid leukemia (AML) is associated with a dismal prognosis. The allogeneic hematopoietic cell transplantation (allo-HCT) is frequently performed as salvage therapy. Reduced intensity conditioning protocols have been developed with the aim of reducing the leukemia burden without increasing their toxicity. We compared the reduced intensity conditioning FM140 (fludarabine, 150 mg/m2; melphalan 140 mg/m2) with FBM110 (fludarabine 150 mg/m2; BCNU, also known as carmustine, 300-400 mg/m2; and melphalan 110 mg/m2). From the European Bone Marrow Transplantation (EBMT) Acute Leukemia Working Party registry, we identified 293 adult patients (FM140, n = 118 and FBM110, n = 175) with AML with relapsed/refractory disease prior to allo-HCT. There were some differences such as age (FM140 = 59.5 years vs. FBM110 = 65.1 years, p < 0.001) and graft-versus-host disease (GvHD) prophylaxis based on in vivo T-cell depletion (TCD, FM140 = 39% vs. FBM110 = 75%, p < 0.001). No differences were observed between FM140- and FBM110-treated patients regarding overall survival (OS) (2-year OS: 39.3% vs. 45.7%, p = 0.58), progression-free survival (PFS) (2-year PFS: 36.1% vs. 37.3%, p = 0.69), non-relapse mortality (NRM) (2-year NRM: 15.3% vs. 25.7%, p = 0.10) and relapse incidence (RI) (2-year RI: 48.6% vs. 37.0%, p = 0.7). In conclusion, despite differences in age and GvHD prophylaxis, AML patients with active disease undergoing allo-HCT after FBM110 conditioning showed similar outcomes compared to FM140.
Keywords: senioři; vidarabin; Vidarabine; Middle Aged; registrace; mužské pohlaví; karmustin; Leukemia, Myeloid, Acute; Adult; recidiva; Registries; Transplantation Conditioning; příprava pacienta k transplantaci; Carmustine; Melphalan; Hematopoietic Stem Cell Transplantation; ženské pohlaví; transplantace hematopoetických kmenových buněk; Humans; Recurrence; melfalan; Transplantation, Homologous; akutní myeloidní leukemie; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; homologní transplantace; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; lidé; Male